HUBUNGAN POLA ASUH DEMOKRATIS ORANGTUA, KONSEP DIRI, DAN PENYESUAIAN SOSIAL DENGAN PERILAKU ASERTIF SISWA SMK MUHAMMADIYAH 1 SLEMAN YOGYAKARTA - ulfa, Maria (Jurnal Psikologi Terapan dan Pendidikan, 2013)
ABSTRAK Teenager be charged to behave assertively by keep respecting other people without physical or verbal violence, expressing feelings, desires, ideas honestly, firmly and openly without feeling anxious. The existence of doubt and self-identity as a teenager, making parents very instrumental in the formation of assertiveness children, and parents must be assertive in the face of the wishes of children so that parents naturally provide a model that supports the growth of assertive behavior. Therefore, this study aimed to determine the relationship of democratic parenting, self-concept, and social adjustment with assertive behavior in students of SMK Muhammadiyah 1 Yogyakarta Sleman. The population in this study were students of class X students of SMK Muhammadiyah 1 Yogyakarta Sleman through cluster random sampling techniques some 118 students. The data analysis technique used in this study is a Structural Equation Model (SEM). Based on the analysis of data, i have obtained conclusions: (1) there is a significant relationship between democratic parenting with self-concept of β = 0.841, (p ≤ 0.01), (2) there is a significant relationship between democratic parenting with social adjustment of β = 0.528 (p ≤ 0.01), (3) there is a significant relationship between self-concept and assertive behavior of β = 0.487 (p ≤ 0.01), (4) there was no significant relationship between social adjustment with assertive behavior due to the resulting probability exceeds the standard probability p ≤ 0.01, (5) there is a significant relationship between democratic parenting with assertive behavior for β = 0.502 (p ≤ 0.01), (6) there is a significant relationship between parenting democratic with assertive behavior mediated by self-concept of β = 0.409 (p ≤ 0.05); (7) There is a significant relationship between democratic parenting with assertive behavior mediated by social adjustment to the value of β = 0.077 (p ≤ 0, 05), and no significant relationship between democratic parenting with assertive behavior is mediated by self-concept and social adjustment in simultaneous of β = 0.486 (p ≤ 0,05). Keyword : democratic parenting patern, self concept, social adjustment, assertive behavior